Determinants of reach counts on medical social media: Evidence from a facebook community page metrics. (5th March 2021) - Nishioka, Daisuke; Tsuboya, Toru
Abstract: Sharing medical information using social media became popular. We aimed to identify what sort of posts can increase reach counts. We used metrics data of 40 posts on the Japan Primary Care Association Commission on Social Determinants of Health (JPCA‐CSDH) Facebook community page. The most popular post was the one about the position paper on health inequality ( Mie‐statement ). The video posts significantly earned 175% more reach counts (vs posts only with letters). Each one percent word counts increase was associated with a 31% increase in reach counts. Videos and more words may deliver medical information effectively. Abstract : Adjusted coefficient and 95% confidence intervals for reach counts in the Japan Primary Care Association Commission on Social Determinants of Health (JPCA CSDH) Facebook community page: results of multivariable linear regression.